Modulating the Mechanical Performance of Macroscale Fibers through Shear‐Induced Alignment and Assembly of Protein Nanofibrils. Issue 9 (9th October 2019) - Kamada, Ayaka; Levin, Aviad; Toprakcioglu, Zenon; Shen, Yi; Lutz‐Bueno, Viviane; Baumann, Kevin N.; Mohammadi, Pezhman; Linder, Markus B.; Mezzenga, Raffaele; Knowles, Tuomas P. J.
Abstract: Protein‐based fibers are used by nature as high‐performance materials in a wide range of applications, including providing structural support, creating thermal insulation, and generating underwater adhesives. Such fibers are commonly generated through a hierarchical self‐assembly process, where the molecular building blocks are geometrically confined and aligned along the fiber axis to provide a high level of structural robustness. Here, this approach is mimicked by using a microfluidic spinning method to enable precise control over multiscale order during the assembly process of nanoscale protein nanofibrils into micro‐ and macroscale fibers. By varying the flow rates on chip, the degree of nanofibril alignment can be tuned, leading to an orientation index comparable to that of native silk. It is found that the Young's modulus of the resulting fibers increases with an increasing level of nanoscale alignment of the building blocks, suggesting that the mechanical properties of macroscopic fibers can be controlled through varying the level of ordering of the nanoscale building blocks. Capitalizing on strategies evolved by nature, the fabrication method allows for the controlled formation of macroscopic fibers and offers the potential to be applied for the generation of further novel bioinspired materials. Abstract : Hierarchical assembly of protein nanofibrils into macroscale fibers using a microfluidic spinning method in a highly controlled manner is reported. Through mimicking the natural spinning process, the confinement and shear‐induced alignment of protein nanofibrils is controlled during the assembly, leading to a modulation of the mechanics of macroscopic fibers.